Neuroinflammation is responsible for pain in endometriosis - targeting the JAK-STAT pathway and mast cell activation - Golinska, Monika; Wołyniak, Maria; Kulesza, Piotr; Fendler, Wojciech (Frontiers in Immunology, 2025)
Chronic pain is a defining feature of endometriosis and contributes significantly to the diminished quality of life observed in affected individuals. Despite advances in understanding disease pathology, current therapeutic strategies largely fail to simultaneously target both lesion development and pain generation. In this review, we examine the neurobiology of endometriosis-associated pain at the level of the brain, dorsal root ganglia, and lesion innervation, with a particular focus on the interplay between inflammation and neurogenesis. We highlight how these processes converge on the JAK/STAT signaling pathway, a critical regulator of both immune activation and nerve fiber growth. The central role of mast cells in coordinating inflammatory and neurogenic responses is also discussed. Emerging evidence supporting the use of JAK inhibitors and mast cell stabilizers in modulating these pathways is reviewed, with emphasis on their potential for repurposing in endometriosis therapy. By targeting the shared mechanisms underlying lesion progression and pain, these pharmacological strategies offer a promising avenue for improving clinical outcomes. Further research is necessary to validate the efficacy and safety of these approaches, but the therapeutic potential of JAK/STAT pathway inhibition and mast cell stabilization could represent a paradigm shift in endometriosis management.